Cell biology molecular biology genetics evolution and ecology Vol 1 - Arumugam N; Meyyan, R P (Kanyakumari Saras Publication, 2014)
CONTENTS: 1.introduction to Cell Biology 2.Microscopy 3.Cytological Techniques 4.The Cell 5.Protoplasm 6.Cell Wall 7.Plasma Membrane 8.Ergastic Substances 9.Plastids 10.Endoplasmic Reticulum 11.Ribosomes 12.Golgi Complex 13.Lysosomes 14.Mitochondria 15.Centrosome 16.Cilia and Flagella 17.Microfilaments 18.Microbodies 19.Vacuoles 20.Nucleus 21.Chromosomes 22.Cell Growth 23.Cell Division 24.Reproduction 25.Gametogenesis 26.Fertilization 27.Parthenogenesis 28.Introduction to Molecular Biology 29.Nucleic Acids 30.Gene 31.DNA is the Genetic Material 32.Genetic Code 33.Replication 34.Transcription 35.Protein Synthesis 36.Regulation of Gene Expression 37.Genetic Recombination 38.Genetic Engineering 39.Immunology 40.Introduction to Genetics 41.Mendelism 42.Genic Interaction 43.Multiple Allels 44.Multiple Gene Inheritance 45.Linkage 46.Crossing Over 47.Cromosome Map 48.Non-Mendelian Ratios 49.Sex Determination in Animals 50.Sex Determination in Plants 51.Sex Linked Inheritance 52.Non-Disjunction 53.Human Genetics 54.Eugenics 55.Euthenics 56.Inbreeding and Outbreeding 57.Mutation 58.Chromosomal Aberrations 59.Gene and Gene Concept,60.Transposons 61.Cytoplasmic Inheritance 62.Index Reviews Add to Cart
Keywords: Vol